2019
DOI: 10.1016/j.jorganchem.2019.05.029
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble carbonyl complexes of 99Tc(I) and Re(I) with adamantane-cage aminophosphines PTA and CAP

Abstract: Pentacarbonyl complexes of 99Tc and Re [M(CAP)(CO)5]X and [M(PTA)(CO)5]X (M = 99Tc or Re and X = ClO4− or OTf-) with aminophosphine ligands 1,4,7-triaza-9-phosphatricyclo[5.3.214,9]tridecane (CAP) and 1,3,5-triaza-7-phosphaadamantane (PTA) were prepared for the first time by the reaction of [MX(CO)5] (M = 99Tc or Re, X = ClO4− or OTf-) with CAP and PTA in CH2Cl2 at room temperature. The reaction of [TcCl(CO)5] with CAP in refluxing CH2Cl2 yields the tricarbonyl complex [99TcCl(CAP)2(CO)3]. Treatment of [Re(H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…All the syntheses were performed at high CO pressures, [4][5][6][7][8] which does not comply with the modern safety requirements adopted in the majority of developed countries. Recently we reported the atmospheric-pressure synthesis of [ 99 TcHal(CO) 5 ], [9] which makes a wide range of higher technetium carbonyls synthetically accessible without using high CO pressures (subsequent transformations of [ 99 TcHal(CO) 5 ] into diverse tetra-and pentacarbonyl complexes are performed at ambient pressure [10][11][12][13] ). At the same time, preparation of the highest technetium carbonyl [ 99 Tc(CO) 6 ] + still required a high pressure of carbon monoxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All the syntheses were performed at high CO pressures, [4][5][6][7][8] which does not comply with the modern safety requirements adopted in the majority of developed countries. Recently we reported the atmospheric-pressure synthesis of [ 99 TcHal(CO) 5 ], [9] which makes a wide range of higher technetium carbonyls synthetically accessible without using high CO pressures (subsequent transformations of [ 99 TcHal(CO) 5 ] into diverse tetra-and pentacarbonyl complexes are performed at ambient pressure [10][11][12][13] ). At the same time, preparation of the highest technetium carbonyl [ 99 Tc(CO) 6 ] + still required a high pressure of carbon monoxide.…”
Section: Introductionmentioning
confidence: 99%
“…Later Aebischer et al [5] observed successive formation of higher technetium carbonyls [ 99 Tc(CO) n (H 2 O) 6-n ] + (n = 4-6) in aqueous solution (2 M HClO 4 ) from the complex [ 99 Tc-(CO) 3 (H 2 O) 3 ]ClO 4 at room temperature and moderately high CO pressure (about 50 atm). The speciation of carbonyl complexes was monitored by 99 Tc and 13 C NMR spectroscopy. The content of the [ 99 Tc(CO) 6 ] + cation (in the mixture of technetium carbonyl species) was low, and no solid salt of this cation was isolated.…”
Section: Introductionmentioning
confidence: 99%
“…Both PTA and CAP are air-stable, resistant to oxidation, easy to synthesize, and especially PTA is highly water soluble. Upon P-coordination, the remaining three nitrogen atoms can participate in acid-base interactions in aqueous solutions, which can further impact their pharmacokinetic behavior (e.g., biodistribution and cell uptake by cancer cells) [ 11 ]. In addition, the nitrogen atoms are reactive under specific conditions, enabling its functionalization (e.g., N-alkylation) and thus, it could be used as a starting point for targeted drug design by tethering biologically active molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Still, the donor atom combinations with PTA in rhenium complexes incorporating the fac -[Re(CO) 3 ] + core remain limited, despite it being the most prominent synthon in radiopharmaceutical and related medicinal chemistry research. As for CAP, its' coordination chemistry with rhenium remains largely unexplored and only in combination with monodentate ligands [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Britvin and coworkers reported the synthesis of the new cage-like water soluble phosphine 1,4,7-triaza-9phosphatricyclo[5.3.2.1]tridecane, to which they gave the acronym of CAP (Figure 1). [26] Although examples of CAP complexes of Au, [26a] Pt and Pd, [27,28] Tc and Re, [29] and Rh [30] were reported, its coordination chemistry with Ru is still underdeveloped. We recently reported the synthesis of the Ru-arene CAP complexes [RuCl 2 (η 6 -p-cymene)(CAP)] (RACAPÀ C) and [RuCl (η 6 -p-cymene)(L)(CAP)]PF 6 (L = CAP or MeCN), that showed to be active in vitro anticancer agents.…”
Section: Introductionmentioning
confidence: 99%